Analysis numeracy literacy skills in terms of standardized math problem on a minimum competency assessment - Megawati, Luthfiana Aristia; Sutarto, Hery (Unnes Journal of Mathematics Education, 2021)
The quality of education in Indonesia as seen from the results of PISA, TIMSS and Indonesian Student Competency Assessment is still relatively low. The Indonesian government issued a new policy to improve the quality of education in Indonesia. One of the policies implemented was the abolition of the National Examination, which is a tool for evaluating learning outcomes at the end of each level of education with a national standard, replaced by the National Assessment. In AN, there are two things that will become national standards in the field of education, namely the Minimum Competency Assessment and the Character Survey. The Minimum Competency Assessment focuses on measuring students' thinking competence when reading texts (literacy) and numeracy literacy. Numerical literacy is needed to deal with Minimum Competency Assessment and is also needed for 21st century skills. Numerical Literacy is also important for everyday life. Therefore, this study focused on analyzing the numeracy literacy skills of students in solving Minimum Competency Assessment math problems and knowing the factors that influence the level of numeracy literacy skills of students in solving Minimum Competency Assessment standard math problems. Collecting data using a questionnaire and testing the Minimum Competency Assessment standard mathematics questions on students. In this study, the results of the analysis of students' numeracy literacy skills were obtained in terms of Minimum Competency Assessment standard math problems and factors that affect students' numeracy literacy skills.